Bridging the Digital Divide through Korea Cooperation: The Case of Ghana-Korea Information Access Centre (iac) - Arko, A.B.; Barfi-Adomako, O.; Kwadzo, G. (African and Asian Studies, 2019)
The purpose of this paper is review the objectives and functions for which the Ghana-Korea Information Access Center (IAC) was set-up at the University of Ghana, Legon in 2012. This type of facility is one of the very few established in Ghana to bridge the digital divide through Ghana-Korea co-operation. Sharing information on its status and development will throw important light on a key Ghana-Korea Project in the Information and Communication Technology (ICT) sector, provide critical guidance for the development of future centres and lay the the basis for exploring possibilities for co-operation in ICT between the the two countries. The paper draws its data from interviews (involving users of the IAC) and documented information on the project. The paper traces the developmental processes (physical, institutional and administrative) for the setting up of the IAC and points up the lessons learnt.
Research Article
Keywords: information centres; Ghana; Korea; University of Ghana; internet; Information and Communication Technology (ICT); digital divide